A mixed isogeometric analysis and control volume approach for heat transfer analysis of nonuniformly heated plates. (3rd June 2019) - Liu, Ning; Beata, Paul A.; Jeffers, Ann E.
Abstract: A framework for conducting heat transfer analysis of nonuniformly heated plates using isogeometric analysis (IGA) is proposed. The modeling approach represents a method that is capable of capturing the full 3D thermal states of plate structures subjected to nonuniform heating. The formulation can be deemed a mixed IGA and control-volume scheme that describes the governing equations using a set of 2D lumped temperature layers. The non-matching grids between the fire domain and the solid domain are weakly coupled. Numerical results demonstrate that the approach is a suitable first step towards coupled CFD-IGA-based fire-structure simulation.